Textural and chemical characterization of sulphide minerals at the Rävliden North VMS deposit, Skellefte district, Sweden - Rincon, Jonathan (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2022)
The discovery of new mineral deposits is essential to meet the increasing demand for metals in our society. The Skellefte mining district in Northern Sweden is one of the main producers of polymetallic ores of Cu, Zn, Pb,Ag, Au, and Te in Europe. Discovery of new deposits in the Skellefte district has become increasingly challenging due to exhaustion of near surface deposits, and general difficulties when applying traditional exploration methods at depth. This has stimulated an interest in alternative methods, such as utilizing the trace element chemistry of sulphide minerals (e.g. pyrite) in metasedimentary and metavolcanic rocks to vector in on massive sulphide deposits. Meanwhile, there is a near complete paucity of trace element data from the massive sulphide deposits of the Skellefte district, and a global shortage of data from Palaeoproteroizoic, polydeformed and metamorphosed volcanogenic massive sulphide deposits (VMS). The Rävliden North Zn-Pb-Cu-Ag VMS deposit in the western most part of the Skellefte district, offers a great opportunity for combine in-situ trace element studies with paragenetic analysis to assess if vectors to mineralisation can be defined, and the effects of deformation and metamorphism. The deposit is hosted at the transition from the mainly felsic metavolcanic rocks of the Skellefte group to the mainly pelitic metasedimentary and mainly mafic – intermediate metavolcanic rocks of the Vargfors group. Rävliden North was significantly affected by deformation and greenschist – lower amphibolite facies metamorphism during the 1.88 – 1.86 Gadeformation phases of the Svecokarelian orogeny. Sphalerite-rich mineralisation associated with pyrrhotite, galena, pyrite and Ag-minerals is situated structurally and stratigraphically above stringer-type chalcopyrite-richmineralisation with lesser pyrrhotite, pyrite and minor amounts of Ag-minerals. Analysis of the textural and structural paragenesis of the mineralisations in the deposit show that sulphides range from aligned sub-parallel to three ...